Handbook of U. S. Labor Statistics 2020: Employment, Earnings, Prices, Productivity, and Other Labor Data - Ryan, Mary Meghan (Bernan Press, 2020)
The Handbook of U.S. Labor Statistics is recognized as an authoritative resource on the U.S. labor force. It continues and enhances the Bureau of Labor Statistics's (BLS) discontinued publication, Labor Statistics. It allows the user to understand recent developments as well as to compare today's economy with past history. The 23rd edition includes the new employment projections from 2018 to 2028. New projections are only released every two years. The Handbook is a comprehensive reference providing an abundance of data on a variety of topics including: Employment and unemployment; Earnings; Prices; Productivity; Consumer expenditures; Occupational safety and health; Union membership; Working poor Recent trends in the labor force And much more! Features of the publication In addition to over 215 tables that present practical data, the Handbook provides: Introductory material for each chapter that contains highlights of salient data and figures that call attention to noteworthy trends in the data Notes and definitions, which contain concise descriptions of the data sources, concepts, definitions, and methodology from which the data are derived References to more comprehensive reports which provide additional data and more extensive descriptions of estimation methods, sampling, and reliability measures